2023
DOI: 10.1186/s12931-022-02297-y
|View full text |Cite
|
Sign up to set email alerts
|

Recognising the importance of chronic lung disease: a consensus statement from the Global Alliance for Chronic Diseases (Lung Diseases group)

Abstract: Background Chronic respiratory diseases are disorders of the airways and other structures of the lung, and include chronic obstructive pulmonary disease (COPD), lung cancer, asthma, bronchiectasis, interstitial lung diseases, occupational lung diseases and pulmonary hypertension. Through this article we take a broad view of chronic lung disease while highlighting (1) the complex interactions of lung diseases with environmental factors (e.g. climate change, smoking and vaping) and multimorbidity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Of these patients, 1.2 million were diagnosed with chronic obstructive pulmonary disease (COPD), which is the third leading cause of death worldwide [ 1 ], and >150,000 were diagnosed with interstitial lung disease (ILD). According to a recent Asthma + Lung UK report, the United Kingdom spends £11 billion (US $13.4 billion) on respiratory diseases each year, with 29% of that budget allocated to COPD [ 17 , 23 ]. Recent studies have demonstrated the importance of timely identification of exacerbations of COPD [ 24 - 26 ]; therefore, longitudinal measurement of symptoms and physiological parameters has the potential to allow for earlier detection [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these patients, 1.2 million were diagnosed with chronic obstructive pulmonary disease (COPD), which is the third leading cause of death worldwide [ 1 ], and >150,000 were diagnosed with interstitial lung disease (ILD). According to a recent Asthma + Lung UK report, the United Kingdom spends £11 billion (US $13.4 billion) on respiratory diseases each year, with 29% of that budget allocated to COPD [ 17 , 23 ]. Recent studies have demonstrated the importance of timely identification of exacerbations of COPD [ 24 - 26 ]; therefore, longitudinal measurement of symptoms and physiological parameters has the potential to allow for earlier detection [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated the importance of timely identification of exacerbations of COPD [ 24 - 26 ]; therefore, longitudinal measurement of symptoms and physiological parameters has the potential to allow for earlier detection [ 27 ]. There is currently an unmet need in the care of patients with respiratory diseases [ 23 , 28 ]. Patients with chronic respiratory diseases and those in the postdischarge period following hospitalization because of COVID-19 are particularly vulnerable, and little is known about the changes in their symptoms and physiological parameters [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic respiratory diseases, such as chronic obstructive pulmonary disease (COPD), asthma and pulmonary hypertension are among the five disease areas with the highest global mortality and morbidity rates ( 76 ). With almost 300 million people affected, asthma is one of the most common respiratory diseases worldwide ( 77 ).…”
Section: Randomized Double-blind Placebo-controlled Human Clinical St...mentioning
confidence: 99%
“…Inhalation of various harmful toxins and microorganisms leads to the development of lung diseases. Lung diseases, including lung cancer, asthma, mycobacterium-based tuberculosis, COPD, and cystic fibrosis, are diseases that target the various regions of the lungs, particularly the airways [4][5][6]. Chronic inflammation typically elevates the susceptibility to debilitating lung conditions.…”
Section: Introductionmentioning
confidence: 99%